SEMANTIC SHIFT IN LOANWORDS FROM ENGLISH TO UZBEK (International journal of artificial intelligence, 2025)
This article explores the phenomenon of semantic shift in loanwords from English to Uzbek, illustrating how borrowed terms adapt and evolve within the cultural and linguistic context of Uzbek. It delves into the factors influencing these changes, such as socio-political dynamics, technology, and globalization, and analyzes specific examples of loanwords that have undergone significant semantic transformations. The study contributes to understanding the interplay between language contact and cultural integration in contemporary Uzbekistan.